Role of Plasma B-type Natriuretic Peptide in Diagnosing Heart Failure - Alam, Mohammed Saiful; Haque, DHMS Sirajul; Amin, Md Nurul (Ibrahim Cardiac Medical Journal, 2011)
Ibrahim Card Med J 2011; 1(1):36-40